{Bis[2-(diphenylphosphino)phenyl] ether-κ2P:P′}(dimethyl 2,2′-biphenyl-4,4′-dicarboxylate-κ2N:N′)copper(I) hexafluoridophosphate acetonitrile solvate - Yu-Guang Ma; Ling Ye; Guang-Di Yang; Ming Zhang; Ai-Guo Yu (Acta Crystallographica Section E, 2009)
In the title compound, [Cu(C14H12N2O4)(C36H28OP2)]PF6·CH3CN, the Cu(I) ion is coordinated by two N atoms from the dimethyl 2,2′-biphenyl-4,4′-dicarboxylate ligand and two P atoms from the bis[2-(diphenylphosphino)phenyl] ether ligand in a distorted tetrahedral environment. In the cation, the short distance of 3.870 (4) Å between the centroids of the benzene and phenyl rings suggests the existence of intramolecular π–π interactions.